2007
DOI: 10.1016/j.beproc.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the psychophysical function in rats

Abstract: The primary goal was to compare results from a free operant procedure with pigeons (Machado and Guilhardi, 2000, Experiment 2) with new results obtained with rats. The secondary goal was to compare the results of both experiments with dependent variables that were not used in the original publication. As in the original study with pigeons, rats were trained on a two-alternative free-operant psychophysical procedure in which left lever press responses were reinforced during the first and second quarters of a 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
(50 reference statements)
5
18
1
Order By: Relevance
“…Findings from a number of earlier studies using variants of a temporal bisection task with pigeons and rats confirmed this prediction (Bizo & White, 1994Guilhardi MacInnis, Church, & Machado, 2007). Specifically, in these studies animals switched from the richer option (that predicted a reward earlier in the trial) to the poorer option (that predicted a reward later in the trial) later in the trial when options predicted a reward according to different variable-interval schedules.…”
Section: Discussionsupporting
confidence: 58%
“…Findings from a number of earlier studies using variants of a temporal bisection task with pigeons and rats confirmed this prediction (Bizo & White, 1994Guilhardi MacInnis, Church, & Machado, 2007). Specifically, in these studies animals switched from the richer option (that predicted a reward earlier in the trial) to the poorer option (that predicted a reward later in the trial) later in the trial when options predicted a reward according to different variable-interval schedules.…”
Section: Discussionsupporting
confidence: 58%
“…They found that, as LeT predicted, the psychometric functions shifted when the reinforcement rates differed around the reversal point, but not when they differed far from the reversal point. These findings, later replicated with rats by Guilhardi, McInnis, Church, and Machado (), are consistent with the model's key idea that both the times of reinforcement and reinforcement rate at those times influence performance.…”
supporting
confidence: 70%
“…When key 1 was reinforced at a higher rate than key 2, the pigeons switched to key 2 later in the interval than when the two keys provided the same reinforcement rate. Conversely, when key 1 was reinforced at a lower rate than key 2, the pigeons switched to key 2 earlier in the interval than when the two keys provided the same reinforcement rate (see also Guilhardi, MacInnis, Church, & Machado, 2007; Machado & Guilhardi, 2000; Stubbs, 1980). The bias effect observed by Bizo and White in the FOPP are very similar to the ones observed in the present study.…”
Section: Discussionmentioning
confidence: 99%